Réponses

  • Utilisateur Brainly
2014-03-17T19:21:56+01:00
Q(x)=(x-5)(2x+7)-(x²-10x+25)+3x-15
     =(x-5)(2x+7)-(x-5)²+3(x-5)
     =(x-5)(2x+7-x+5+3)
     =(x-5)(x+15)
  • Utilisateur Brainly
2014-03-17T19:23:51+01:00
2) Factorisation: 

Q(x) = (x-5) (2x+7) - (x²-10x+25) + 3x-15 ⇒ Identité remarquable et factorisation par 3

Q(x) = (x-5) (2x+7) - (x-5)² + 3(x-5) ⇒ On remarque le facteur commun 
Q(x) = (x-5) (2x+7 -x+5 +3) ⇒ On factorise par (x-5)
Q(x) = (x-5) (x+15)   

Voilà ! J'espère t'avoir aidé(e) ! :)